Topological Isomerism in Three-Dimensional Covalent Organic Frameworks - Liu, Yaozu; Li, Jingwei; Lv, Jia; Wang, Zitao; Suo, Jinquan; Ren, Junxia; Liu, Jianchuan; Liu, Dong; Wang, Yujie; Valtchev, Valentin; Qiu, Shilun; Zhang, Daliang; et al. (Journal of the American Chemical Society, 2023)
Although isomerism is a typical and significant phenomenon in organic chemistry, it is rarely found in covalent organic framework (COF) materials. Herein, for the first time, we report a controllable synthesis of topological isomers in three-dimensional COFs via a distinctive tetrahedral building unit under different solvents. Based on this strategy, both isomers with a or net (termed JUC-620 and JUC-621) have been obtained, and their structures are determined by combining powder X-ray diffraction and transmission electron microscopy. Remarkably, these architectures show a distinct difference in their porous features; for example, JUC-621 with a net exhibits permanent mesopores (up to ∼23 Å) and high surface area (∼2060 m g ), which far surpasses those of JUC-620 with a net (pore size of ∼12 Å and surface area of 980 m g ). Furthermore, mesoporous JUC-621 can remove dye molecules efficiently and achieves excellent iodine adsorption (up to 6.7 g g ), which is 2.3 times that of microporous JUC-620 (∼2.9 g g ). This work thus provides a new way for constructing COF isomers and promotes structural diversity and promising applications of COF materials.